1999
DOI: 10.1108/08876049910298757
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of influences on public opinion towards alcohol and tobacco sponsorship of sporting events

Abstract: The marketing of alcohol and tobacco products and their related public policy implications have become controversial issues worldwide, due mainly to health-related issues. Uses a telephone survey methodology to compare attitudes toward Olympic sponsorship by a leading US brewer with general attitudes toward the use of sports sponsorship to promote tobacco products. Results suggest that respondents have significantly different attitudes towards the two product categories and their use of sponsorship, accepting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 38 publications
2
30
0
Order By: Relevance
“…For instance, the researchers found that beer drinkers had significantly more positive attitudes towards beer sponsorships than non-drinkers, as did smokers versus non-smokers, but, in general, attitudes towards beer sponsorship were significantly more positive than attitudes towards tobacco sponsorships, a distinction that was attributed to the greater social acceptability of drinking than smoking. Furthermore, McDaniel and Mason (1999) also found a strong corollary between smokers and their positive attitudes towards sponsorship by tobacco companies, suggesting that the same corollary may apply to gamblers and LGE sport sponsorship. Such findings suggest that, as a general research proposition, those who gamble may have more positive attitudes toward LGE sponsorship than non-gamblers.…”
Section: Effects On Consumer Attitudes and Behaviours: Some Starting mentioning
confidence: 99%
See 4 more Smart Citations
“…For instance, the researchers found that beer drinkers had significantly more positive attitudes towards beer sponsorships than non-drinkers, as did smokers versus non-smokers, but, in general, attitudes towards beer sponsorship were significantly more positive than attitudes towards tobacco sponsorships, a distinction that was attributed to the greater social acceptability of drinking than smoking. Furthermore, McDaniel and Mason (1999) also found a strong corollary between smokers and their positive attitudes towards sponsorship by tobacco companies, suggesting that the same corollary may apply to gamblers and LGE sport sponsorship. Such findings suggest that, as a general research proposition, those who gamble may have more positive attitudes toward LGE sponsorship than non-gamblers.…”
Section: Effects On Consumer Attitudes and Behaviours: Some Starting mentioning
confidence: 99%
“…As with tobacco and alcohol sport sponsorship, contradictions with sportʼs growing alliances with LGEs clearly exist on two fronts. First, there are the potential risks associated with gambling that are, as with tobacco and alcohol sports sponsorship, inconsistent with the health and social benefits of sport consumption (McDaniel & Mason, 1999). Second, and in this case unlike tobacco and alcohol sponsorship, the association of sport organisations with LGEs raises, albeit indirectly, "integrity of the game" challenges.…”
Section: The Cause For Concernmentioning
confidence: 99%
See 3 more Smart Citations